2015
DOI: 10.1186/s12868-015-0225-8
|View full text |Cite
|
Sign up to set email alerts
|

Emotional words facilitate lexical but not early visual processing

Abstract: BackgroundEmotional scenes and faces have shown to capture and bind visual resources at early sensory processing stages, i.e. in early visual cortex. However, emotional words have led to mixed results. In the current study ERPs were assessed simultaneously with steady-state visual evoked potentials (SSVEPs) to measure attention effects on early visual activity in emotional word processing. Neutral and negative words were flickered at 12.14 Hz whilst participants performed a Lexical Decision Task.ResultsEmotion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…Thus, when participants actively focused on the words' valence, they probably also retrieved more information about their semantic meaning. A previous ERP study of attentional cuing toward negative words found a P2 effect for content cueing [Kanske et al, ], supporting effects of affective‐semantic orienting in the P2/EPN time window [see, Trauer et al, for a discussion of the similarity of P2 and EPN effects in word processing].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Thus, when participants actively focused on the words' valence, they probably also retrieved more information about their semantic meaning. A previous ERP study of attentional cuing toward negative words found a P2 effect for content cueing [Kanske et al, ], supporting effects of affective‐semantic orienting in the P2/EPN time window [see, Trauer et al, for a discussion of the similarity of P2 and EPN effects in word processing].…”
Section: Discussionmentioning
confidence: 69%
“…G 5 Gyrus; Inf 5 inferior, Mid 5 middle, Sup 5 superior. Within significant main effects of emotions, post hoc differences were only found for the comparison emotional nouns > neutral nouns r Selective Visual Attention to Emotional Words r r 3583 r A previous ERP study of attentional cuing toward negative words found a P2 effect for content cueing [Kanske et al, 2011], supporting effects of affective-semantic orienting in the P2/EPN time window [see, Trauer et al, 2015 for a discussion of the similarity of P2 and EPN effects in word processing]. Superior frontal sources could reflect the evaluative nature of the present task.…”
Section: Discussionmentioning
confidence: 94%
“…(Ding, Sperling, & Srinivasan, 2005) found a reversed effect of attention on SSVEP amplitude at frequencies in the lower alpha band. However, in a recent study, SSVEP amplitude was completely unaffected by emotional word content, and more importantly for the present discussion, by the lexical status of the string (Trauer et al, 2015). While the presentation time and stimulation frequency used by Trauer and coll.…”
Section: Discussionmentioning
confidence: 49%
“…Indeed, both studies reported results relative to few occipital electrodes that reflect activity in early visual cortex only. On the contrary, the effect of emotional words should start at later lexico-semantic stages (Trauer et al, 2015).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation